Effects of socio-cultural norms on smallholder adaptation to climate change in Nkoranza South municipality, Ghana. Issue 2 (17th February 2021) - Sowah, Alexander Nii Adjei; Owusu, Kwadwo; Yankson, Paul William Kojo; Quansah, Edna
ABSTRACT: Socio-cultural norms can potentially enhance the adaptive capacities of some groups while constraining the capacities of others. Using household surveys, focus group discussions, and key informant interviews in four communities in the Nkoranza South municipality, Ghana, this article examines how socio-cultural norms influence the climate change adaptation of smallholder farmers. While socio-cultural norms fostered indigenes' access to farmlands and other communal resources resulting in on-farm diversification, migrants/settlers could not take advantage of climate-resistant cash crops such as cashew due to their limited access to and control of land. Additionally, cultural expectations and roles enhanced women's non-farm adaptive options compared to men.